Paisagens culturais alternativas no Brasil contemporâneo e vivência espacial da comunidade indígena Krenak do sudeste (Vale do Rio Doce/MG) - Ludimila de Miranda Rodrigues (2013)
Within the different socio-cultural experiences of indigenous people on consolidating counter emerging projects and different levels of contact with our society, established by them historically in the national context, this paper aims to study the specific and vertical cultural alternatives landscapes from Krenak indigenous people , remaining family Borun which still live on their traditional territory at Vale do Rio Doce (Minas Gerais). That said, we have tried to carry out an investigation, clearly and explicitly geographical, around the alternatives cultural landscapes characterized by the interpretive lines of the Cultural Contemporary Geography, especially concerning the most heterodox visions "cultural Marxism" of Denis Cosgrove, linked to the historical and current experience of the indigenous people from southeastern Brazil,more specifically to the Krenak people, at Vale do Rio Doce. With the survey made through the vast indigenous literature and also by the field work conduction on the indigenous land Krenak (with systematic mapping of the area and conducting questionnaires and interviews) was possible to understand the historical elements, territorial and cultural individuals which contributed to the segment of remaining indigenous concentration (marginal and residual) in the studied region. We also consider the society's perception and interaction from Resplendor (municipality in which the indigenous territory is officially inserted) in the construction of alternatives cultural landscapes Krenak people. This study is justified by the huge academic-scientific importance assumed by discussions around the concept of Cultural Landscape, and also by the property / convenience in attemptting to establish a dialogue between the academic and theoretical apparatus and inflections of the reality, underway, in the country and in the world - and in particular, with phenomenas and processes interwoven with the "emergence of collective identities."